ECOLOGICAL AWARENESS IN â€œNEVER LONELY AGAINâ€ PICTURE BOOK (PANOPTICON: Journal of English Studies, 2022)
This study entitled â€œEcological Awareness in Never Lonely Again Picture Bookâ€. It represents how ecological awareness the main character portrays the way nature as a friend can occur. The data of this study were collected from a picture book entitled Never Lonely Again by Hans Wilhelm (1988). The qualitative approach was used to present and analyze the data. In analyzing the data (Issue of Nature as a Friend) theory from Cheryll Glotfelty (1996) was applied. The result of the study revealed that nature can be an influence in changing a good personality towards the main character. The personality change caused natural objects in the picture book such as flowers, sunshine, waterfall, mountain, etc. To complete the research, analysed the data based on the pictures and saw the changes in the characters at the beginning and end of the story.Keywords: Literature, ecological awareness, picture book